PERBEDAAN MORDAN BELIMBING MANIS (Avverhoa Carambola) DAN BELIMBING WULUH (Avverhoa Bilimbi) TERHADAP HASIL PENCELUPAN PADA BAHAN SUTERA MENGGUNAKAN EKSTRAK BIJI KESUMBA (Bixa Orellana L) - Alvina, Alvina; Adriani, Adriani; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2016)
This study aimed to describe the name of the color (hue), light and dark colors (Value) and flatness of color for silk dyeing results using crimson seed extract (Bixa Orellana l) with mordant sweet star fruit and starfruit. This research is an experimental research. The data used are primary data sourced from 15 panelists, then the collected data is processed and analyzed using ANOVA and Percentage. Dyeing silk with crimson seed extract (Bixa Orellana l) without mordant produce Mineral Orange color with a value reasonably bright and flatness of color is quite average. Mordan sweet star fruit is Peach with bright value and average color flatness and mordant starfruit is Light Peach with a value very bright and flatness of color is very flat. The results of the data analysis of light and dark colors (value) indicates F count> F table = 3.320> 3. 22 This means that there is a significant difference to the light and dark colors (value) due to differences mordant. At the flatness of the color indicates Fhitung> Ftable = 9599> 3.22 means that there is a significant difference to the flatness of color due to differences mordant. Kata Kunci : Perbedaan Mordan, Ekstrak Biji Kesumba